Charging System for Electric Vehicle and Hybrid Electric Vehicle in Running Condition: A Review - Aryan Sachin Sasane; Rahul Bibave; D. B. Pardeshi (International Journal of Electrical Machine Analysis and Design, 2024)
This study examines comparative studies of three different charging systems used in electric vehicles while they are moving or operating. It also deals with the idea of using an alternator at each wheel of the vehicle to charge the non-connected set of batteries, as well as a brief explanation of the principles, mechanisms, design, and constraints of fuel cells, solar panels, and regenerative brakes. These are some of the most widely used methods for charging an EV or HEV while operating a motor vehicle. This technique will only increase the range by a few miles and not much more because it consumes very little energy. However, using the alternator will boost the range to more than 90% of an infinite loop. To overcome range restrictions and charging downtime, creative on-the-go charging solutions are crucial as the demand for electric vehicles (EVs) and hybrid electric vehicles (HEVs) rise. Current and developing technologies in dynamic charging systems, such as solar-based in-motion charging for EVs and HEVs, conductive rail systems, and wireless inductive charging, are examined in this overview. This study highlights developments in on-road charging mechanisms and assesses their potential to increase the adoption of EVs and HEVs by examining the technological viability, infrastructure needs, and operational efficiency of these systems. In addition to offering insight into the future of dynamic in-motion charging systems for sustainable mobility, it ends by going over lingering difficulties such infrastructure costs, standardisation problems, and energy transfer efficiency.
Keywords: Electric vehicle; Fuel Cell; alternator; battery; hybrid electric vehicle; range; regenerative braking; solar cell